Peran Bakawuah Adat Dalam Mengokohkan Jati Diri Masyarakat Dan Mendorong Pelestarian Budaya Di Nagari Latang - Alfa Rehan Oktori Rahmadana; Andri Saputra; Mutia Srimaningsi; Nabilla; Reva Lina Putri; Dori Yuvenda (Universitas Garut, 2025)
This study discusses the role of Bakawuah Adat as a post-harvest festival in strengthening identity and preserving local culture in Nagari Latang, Sijunjung, West Sumatra. Using descriptive qualitative methods, data were obtained from interviews with traditional leaders, niniak mamak, alim ulama, cadiak pintar, and observations during the 2025 UNP Community Service Program. The results show that Bakawuah Adat is a form of gratitude to Allah SWT for the harvest, as well as a medium for strengthening traditional values ​​and syarak. This tradition involves all elements of the nagari—niniak mamak, bundo kanduang, youth, and children of the nagari—in every traditional procession. In addition to being a ceremony, Bakawuah also serves as a means of character education and cultural inheritance to the younger generation through bajamba activities, art performances, and ancestral grave pilgrimages. The synergy between traditional leaders, the nagari government, and educational institutions ensures that Bakawuah remains sustainable amidst the current of modernization. This tradition is proof that local wisdom can be a stronghold of community identity in the global era.